Variability of nutrients in Parkia biglobosa kernels from three geographical regions in Burkina Faso - Guissou, Aimée W.D.B.; Parkouda, Charles; Vinceti, Barbara; Traoré, Esther M. A.; Dao, Aboubacar S.; Termote, Céline; Manica, Mattia; Savadogo, Aly (Academic Journals, 2020)
This study aimed to determine the nutritional composition of the kernels of the African locust bean, Parkia biglobosa, collected in three populations (Louda, Nobéré and Péni) representative of different environmental conditions, from more arid in the northern population (Louda) to wetter in the most southern population (Péni). Biochemical analyses were carried out using standard methods. Results expressed on a dry basis showed that glutamic acid was the amino acid with highest values in kernels (2.72 - 6.44%). Methionine was the amino acid with lowest values (0.11 - 0.33%). The kernels had an interesting amount of minerals, Fe (4.15 - 18.48 mg), K (662.55 - 2801.69 mg), Mg (178.19 -1624.83 mg), Zn (2.58 - 4.86 mg) and Ca (316.13 - 1731.41 mg). Moisture content varied from 4.49 to 7.56%, carbohydrates from 10.85 to 19.81%, proteins from 30.32 to 43.91%, ashes and lipids respectively from 4.19 to 5.80% and from 21.64 to 30.77%. Samples from Louda contained the highest mean values for proximate composition. Samples from Nobéré contained higher amounts of mineral and amino acids compared to the other two populations. The most important variation between samples of the same location was observed in the mineral composition (CV% 20% except Zn); Louda was the location with highest dispersion of values. Samples from Péni in the South-Soudanian zone showed overall lower nutritional value. The nutritional composition of P. biglobosa kernels varied significantly according to the location where seeds were collected.